Learning Technologies in the EFL Class after the Pandemic: Lessons Learned and Future Directions - Spataro, Claudia; Orgnero, Carolina; Simón, Liliana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Moving our EFL classes online with little or no time due to the pandemic meant an unprecedented change in our ways of teaching and a possible challenge in our future practices. Now that the pandemic is over, it is important to rethink and shape our classrooms beyond ERT (Emergency Remote Teaching) considering the lessons learned. This reflective article starts with a historical overview on CALL (Computer Assisted Language Learning) to understand how it has affected L2 teaching and learning for more than 40 years and paved the way to deal with the pandemic, it then raises awareness on some issues related to ERT and reflects on the lessons learned in three areas: live sessions, digital tools/games and metacognitive skills. We contend that, by reflecting on where we have been and what we have learned, we will be able to make informed decisions to continue integrating technologies in our English classes.